Assess, rebuild, connect : creating a new life beyond addiction (KiCam Projects, 2018)
"Assess, Rebuild, Connect" is the comprehensive resource that guides you through the three phases of addiction recovery and into a life of sustained sobriety for yourself and your loved ones. Featuring, reflection questions and room for written responses, plus real-life success stories to inspire and encourage, "Assess, Rebuild, Connect" provides a trusted companion through pre-treatment, treatment, and aftercare. You will be empowered to: ASSESS issues and obstacles and set realistic expectations about the journey ahead. REBUILD the most important parts of your life: trust in yourself, in others, and in the process ; self-respect and confidence; and coping skills for handling everyday ups and downs. CONNECT with the "real world" outside of addiction, repairing relationships and managing the challenges of maintaining lifelong sobriety. Based on decades of clinical experience, "Assess, Rebuild, Connect" is a down-to-earth tool for creating a new life beyond addiction - the life everyone deserves!